2010
DOI: 10.1002/ana.22087
|View full text |Cite
|
Sign up to set email alerts
|

Early onset collagen VI myopathies: Genetic and clinical correlations

Abstract: Objective Mutations in the genes encoding the extracellular matrix protein collagen VI (ColVI) cause a spectrum of disorders with variable inheritance including Ullrich congenital muscular dystrophy, Bethlem myopathy, and intermediate phenotypes. We extensively characterized, at the clinical, cellular, and molecular levels, 49 patients with onset in the first 2 years of life to investigate genotype‐phenotype correlations. Methods Patients were classified into 3 groups: early‐severe (18%), moderate‐progressive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
137
4
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(152 citation statements)
references
References 38 publications
9
137
4
2
Order By: Relevance
“…Skipping of COL6A3 exon 16, due to splice site mutations or small deletion, is the most common molecular defect in dominant UCMD patients (11,13,23,25). In this study we deleted exon 16 and its flanking sequence in the mouse Col6a3 gene by gene targeting.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Skipping of COL6A3 exon 16, due to splice site mutations or small deletion, is the most common molecular defect in dominant UCMD patients (11,13,23,25). In this study we deleted exon 16 and its flanking sequence in the mouse Col6a3 gene by gene targeting.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that the Col6a3 hm/hm mice display reduced muscle contractile forces after twitch and tetanic stimulation at age 4 months (22). In UCMD patients, whereas recessive mutations causing an absence of collagen VI almost invariantly display an "early-severe (never acquired ambulation)" phenotype, dominant mutations causing skipping of COL6A3 exon 16 result in both early-severe and "moderate-progressive (loss of ambulation at a mean age of 10 years)" manifestations (13). These observations suggest that dominant exon skipping mutation may result in a somewhat less severe phenotype compared with recessive mutations that lead to mRNA decay and that modifier genes likely contribute to the phenotypic variations of dominant exon skipping mutations.…”
Section: Figure 10 Ultrastructural Analysis Of the Col6a3mentioning
confidence: 99%
See 2 more Smart Citations
“…Autophagy has a key role in the clearance of damaged organelles and in the turnover of cell components and is thus essential for tissue homeostasis. Recently, 56 novel mutations have been described, allowing a clinical classification and revealing the complexity of genotype-phenotype relationships (Briñas et al, 2010).…”
Section: A Large Spectrum Of Mutations In Collagen Genes Causes Inhermentioning
confidence: 99%